PERILAKU SENSITASI PADA LOGAM STAINLESS STEEL SERI J4 AKIBAT PERLAKUAN PANAS - Gadang Priyotomo; I Nyoman Gede Putrayasa A (Pusbindiklat - LIPI, 2018)
The failure of austenitic stainless steel during the industrial aplications is place sensitization due to heat treatment. The investigation of that failure has been investigated by researchers in particular for stainless steel 2XX and 3XX types, while there isno or little investigation for stainless steel J4 type.Furthermore, the investigation of the presence of sensitization on stainlees steel was conducted by referring to American Society for Testing and Materials (ASTM) A262-02a, which the caracterization of metal surface morphologies dan chrom content used optical microscope andscanning electron microskop, and Energy-dispersive X-ray spectroscopy, respectively. The results elucidate that sensitization is produced in temperature range from700oC up to 900oC .There isgrain boundaries attack onsurface morphologies after sensitization test in the temperature range from700oC up to 900oC ,whichis unlikely to happenat temperature of 600oC. The possibility of chromium difusion to grain boundaries took place from the decrease of chromium content adjancent with grain boundaries and the increase of chromium content in grain boundaries, whichimplies the formation of intermetallic compound of carbide.